Faith, Belief Transcendence According to Wilfred Cantwell Smith - Gualtieri, Antonio R (Journal of Dharma, 1981)
Wilfred Cantwell Smith is one of the most important Canadian thinkers in the field of religion today. It may aiso be readily argued that this encomium applies with much wider scope. I suspect that if his works on Islam — especially Islam in Modern History I — had been widely read, recent events in Iran and other parts of the Muslim world would have been neither unexpected nor unintelligible to Western observers. It is difficult not to be impressed — even intimidated — by the arguments of one who does his own translations from Swedish, Arabic, Latin and Sanskrit, to specify only a few of the original languages from which Smith draws his evidence. The excursions through his compendious and erudite notes (a feature which has become a sort of trademark — sometimes irritating — of his books) provides a fascinating exposure to a wide range of historical and comparative religious information.